Accelerating patient access to oncology medicines with multiple indications in Europe. Issue 1 (1st January 2021) - Lawlor, R.; Wilsdon, T.; Darquennes, E.; Hemelsoet, D.; Huismans, J.; Normand, R.; Roediger, A.
ABSTRACT: Background: In recent years, innovation in oncology has created new challenges for pricing and reimbursement systems. Oncology medicines with multiple indications face a number of access challenges: (1) the number of assessments and administrative burden; (2) aligning price to different values of the same product; (3) managing clinical uncertainty at time of launch; and (4) managing budget uncertainty. These challenges impact a range of stakeholders and can result in delayed patient access to life-saving treatments. Consequently, countries have taken steps to facilitate patient access. Methods: Drawing on the experience across Europe we have reviewed different mechanisms countries have adopted that address these challenges. These include approaches aimed directly at the issue, multi-year-multi-indication (MYMI) agreements (BE, NL), and other approaches to manage access: flexible access agreements for new indications with clinical uncertainty (UK); development of a new agreement for each new indication (IT); and immediate access for new indications and bundled assessments (DE). Results: MYMI agreements are valuable where existing rules mean that every indication faces the same upfront evaluation process that delays patient access. They are also useful in managing budget impact and uncertainty. Other approaches that adopt an indication-specific approach helps manage clinical uncertainty at the time of launch and realise different values for the same product. They can help align price to value, even though indication-based pricing does not exist. Bundled assessments reduce the administrative burden for stakeholders, and the benefits of immediate reimbursement is that patient access is not delayed. Conclusion: The challenges for medicines with multiple indications impact a range of stakeholders and can result in delayed patient access to life-saving treatments. MYMI agreements have created a more pragmatic approach to HTA for medicines with multiple indications to ensure both fast and broad patient access. Continued innovation in oncology will require further innovative approaches in pricing and reimbursement. It is important that policymakers, payers and manufacturers engage in early discussions and are willing to find new solutions to help accelerate patient access to innovative therapies.